Functional Training of 11-15-Year-Old Football Players (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
the article examines the functional training of football players of the training group, its importance and the development of muscle and bone tissues of children's bodies. The changes that occur in children's respiratory, bone-muscular and blood circulation systems while playing football have been analyzed.